The Detective Fiction: Forensic Literature in Turkey and The World with Its Implacable Historical Background - Ağaoğlu, Reyyan; Oral, Gökhan (The Bulletin of Legal Medicine, 2018)
Language and discourse constitute a whole; literature, which forms a part of discourse through literary works and suggests an idea about so many facts just like historical, social and psychological events, is studied by other disciplines besides Linguistics; Forensic Science, having a multidisciplinary feature, is one of them. As the detective fiction forms a part of literature, the relationship of this part with Forensic Sciences inevitably remains at the forefront. Throughout the emergence of human beings, crime occupies a place in the life of the mankind and this issue manifests itself in literary works. The detective fiction, formed through crime-criminal-detective triangle, is a source by which Forensic Sciences profit. This study is carried out to investigate developmental stages of the detective fiction by assessing the position of the detective fiction in Turkish and world literature.In the scope of the study, a literature review was made and developmental stages of the detective fiction in Turkish and world literature were traced. In this regard, a qualitative study was prepared and a chronological schema which reveals the most important and lively works of Turkish and world literature was created.At the end of the study, it was learned that the detective fiction emerged through police power and the policemen and the detectives, who had left their marks in history, set light to literary works which still remain a mystery.
Keywords: literature; forensic sciences; detective fiction; crime